A consistent definition of cultural safety within Australian health professional education: a scoping review. (September 2022) - Brumpton, Kay; Evans, Rebecca; Ward, Raelene; Sen Gupta, Tarun
This scoping review aims to explore how cultural safety is defined in the Australian literature with health professional learners in clinical interactions. It maps how the components of the Australian Health Practitioner Regulation Agency definition of cultural safety align with this evidence. Databases were systematically searched for original, peer-reviewed research that included Australian Aboriginal and Torres Strait Islander peoples, health professional learners who were eligible for registration in Australia, teaching and assessment. Many elements of cultural safety lacked Indigenous input and had no patient involvement. General consultation and communications skills were key components of culturally safe interactions. The Australian Health Practitioner Regulation Agency consensus statement on cultural safety provides a consistent definition for teaching and learning cultural safety within health professions in Australia. The findings suggest that developing an approach for cultural safety requires incorporation of Indigenous voices, patient-centred care metrics, patient feedback, learner self-assessment and attitude measures.